2022
DOI: 10.3389/fmicb.2022.971817
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of porcine reproductive and respiratory syndrome virus from Eastern China during 2017–2022

Abstract: Porcine reproductive and respiratory syndrome (PRRS) is an immunosuppressive disease caused by PRSS virus (PRRSV). PRRSV mainly causes reproductive disorders in pregnant sows and respiratory diseases in piglets. Recently, it has emerged as one of the most important diseases of the pig industry across the globe. In this study, we have collected 231 samples from differently sized pig farms in Eastern China from 2017 to 2022 to investigate the epidemic characteristics of the disease. All samples were screened by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…Unlike other studies which focused on a single or on few clusters [ 13 ] or subgroups or lineages [ 14 , 22 , 34 ] or limited to a few farms [ 8 ] our study covered all wild-type clusters found over a 10 year-period at the provincial level. Furthermore, each cluster was described based on its detection in at least one of pig site within a year instead of the number of detections, in order to prevent the influence of repeated sampling of the same strain within a herd during the same year.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike other studies which focused on a single or on few clusters [ 13 ] or subgroups or lineages [ 14 , 22 , 34 ] or limited to a few farms [ 8 ] our study covered all wild-type clusters found over a 10 year-period at the provincial level. Furthermore, each cluster was described based on its detection in at least one of pig site within a year instead of the number of detections, in order to prevent the influence of repeated sampling of the same strain within a herd during the same year.…”
Section: Discussionmentioning
confidence: 99%
“…Porcine reproductive and respiratory syndrome (PRRS) is a viral disease caused by PRRS virus (PRRSV) with serious reproductive disorders in sows and respiratory symptoms in piglets, leading to significant economic losses in the pig industry worldwide. Genetic diversity, immunosuppression, and the antibody-dependent enhancement (ADE) effect of PRRSV pose additional challenges for PRRS prevention and control [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. Although vaccination is the most effective method to prevent PRRSV infection, the efficacy of PRRSV vaccines remains unsatisfactory [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The PRRSV is a single-stranded positive-sense RNA virus with a capsid [ 37 , 38 , 39 ]. The PRRSV disease was first identified in the United State of America in the late 1980s and in Germany in the 1990s [ 40 , 41 , 42 , 43 , 44 ], and then it spread to other pig-producing areas, including China, causing enormous economic losses to the pig industry [ 45 , 46 , 47 , 48 ].…”
Section: Introductionmentioning
confidence: 99%